2001
DOI: 10.1093/ps/80.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Locally Grown Whole Barley With or Without Enzyme Addition and Whole Wheat on Broiler Performance and Carcass Traits

Abstract: Two experiments were conducted to investigate the impact of increasing dietary levels of whole barley (WB) with or without exogenous enzymes and of whole wheat (WW) without E fed from 7 d of age, on performance and carcass characteristics of broilers. Experiment 1 was conducted with corn-soybean meal grower diets containing WB at 0, 10, 10 + enzymes, 15, or 15% + enzymes. The finisher diets contained, as fed, WB at 0, 15, 20 + enzymes, 15, or 20% + enzymes. In Experiment 2, grower diets contained 0, 10, 10, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…Similar results have been reported by Amerah et al (2008). In contrast, other researchers have reported higher relative abdominal fat weight when WW was included Nahas & Lefrancois, 2001). Column means with different superscripts differ significantly at P <0.05; * P <0.1, NS -non-significant.…”
Section: Resultssupporting
confidence: 87%
“…Similar results have been reported by Amerah et al (2008). In contrast, other researchers have reported higher relative abdominal fat weight when WW was included Nahas & Lefrancois, 2001). Column means with different superscripts differ significantly at P <0.05; * P <0.1, NS -non-significant.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, Wu et al (2004) found no effect of whole wheat inclusion on abdominal fat weights. Other researchers have reported higher relative abdominal fat weight when whole wheat was included (Jones and Taylor, 2001;Nahas and Lefrancois, 2001). These conflicting results with regard to abdominal fat with whole wheat feeding may be partially due to incorrect protein to energy ratio in the basal diet (Erener et al, 2003).…”
Section: Resultsmentioning
confidence: 96%
“…The anti-nutritive activity of pentosans in wheat is also related to the increase in digesta viscosity Annison, 1990, 1992). The increased viscosity reduces intestinal digestion and absorption because of the interaction between pentosans and endogenous enzymes that promotes the formation of a complex that reduces the activity of these enzymes (Nahas and Lefrançois, 2001). Therefore, microbial enzymes have been found to be beneficial in terms of nutrient utilisation when supplemented into barley or wheat based broiler diets (Edney et al, 1989;Pe�erson et al, 1990;Nahas and Lefrençois, 2001).…”
mentioning
confidence: 99%